THE INFLUENCE OF SINGLE MOTHERHOOD ON THE ACADEMIC PERFORMANCE OF CHILDREN IN ISLAMIC FAITH-BASED SCHOOLS, MOMBASA COUNTY, KENYA - Akida, Mwanaidi; Ali, Dr. Ali Adan; Karama, Prof Mohamed (African Journal of Education and Practice, 2018)
Purpose: This study investigated the influence of single motherhood on pupils' academic performance in Islamic Faith-Based schools in Mombasa County, Kenya. The study wanted to establish whether pupils' academic performance differed between children from intact family and those from single motherhood. Methodology: Case control study design was used to determine the difference between the control group and experimental group. A questionnaire and interview was used to collect the primary data while pupils' report books were used to obtain test score as a secondary data. Purposive sampling technique was used to select the sample size of 36 participants. Purposive sampling was preferred because of nature of the study and targeted population. Data analysis involved using frequencies and Pearson co-efficiency. Results: The results indicated that, there is high significance difference on academic performance between children from single motherhood and those from intact families. The main conclusion derived from this research is that, single motherhood has negative influence on pupils' academic performance in Islamic-Based Schools. Unique Contribution to Theory, Policy and Practice: The study recommends that teachers should give more attention to children from single motherhood to enable them cope and be able to compete with children from intact families. In addition, teachers, Imams and parents should ensure counseling services are provided to them in order to adjust to the academic environment.